Institutional Support of Agro-industrial Complex Entities of Quasi-public Sector of Kazakhstan - TAUBAYEV, Ayapbergen; AKENOV, Serik; ULYBYSHEV, Dmitriy; KERNEBAEV, Aydin (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
In article on materials of JSC ‘National managing holding ‘KazAgro’ examining institutional and investment support mechanisms of the agro-industrial complex of Kazakhstan at the present stage. Determined that, as in the world economy, in Kazakhstan, the quasi-public sector is the key economic mainstay of the country and is the most important area of government in the priority areas of the national economic system. Established that the main purpose of the Holding ‘KazAgro’ is the realization of the state policy on forming and development of competitive and export-oriented agriculture. Analyzed key quantitative and qualitative parameters of the investment support of subjects of agro-industrial complex of Kazakhstan through its subsidiary structural units of the holding ‘KazAgro’ for the last number of years. Identified priority areas for improving the institutional and investment activity of the holding ‘KazAgro’ for the future.